UV Filters, Ingredients with a Recognized Anti-Inflammatory Effect - Couteau, Céline (Public Library of Science, 2012)
BACKGROUND: To explain observed differences during SPF determination using either an in vivo or in vitro method, we hypothesized on the presence of ingredients having anti-inflammatory properties. METHODOLOGY/PRINCIPAL FINDINGS: To research our hypothesis, we studied the 21 UV filters both available on the market and authorized by European regulations and subjected these filters to the phorbol-myristate-acetate test using mice. We then catalogued the 13 filters demonstrating a significant anti-inflammatory effect with edema inhibition percentages of more than 70%. The filters are: diethylhexyl butamido triazone (92%), benzophenone-5 and titanium dioxide (90%), benzophenone-3 (83%), octocrylène and isoamyl p-methoxycinnamate (82%), PEG-25 PABA and homosalate (80%), octyl triazone and phenylbenzimidazole sulfonic acid (78%), octyl dimethyl PABA (75%), bis-ethylhexyloxyphenol methoxyphenyl triazine and diethylamino hydroxybenzoyl hexylbenzoate (70%). These filters were tested at various concentrations, including their maximum authorized dose. We detected a dose-response relationship. CONCLUSIONS/SIGNIFICANCE: The anti-inflammatory effect of a sunscreen ingredient may affect the in vivo SPF value.